Yeast as a model for studying Alzheimer's disease - Bharadwaj, Prashant; Martins, R.; Macreadie, I. (Wiley-Blackwell, 2010)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by acute cognitive decline. The AD brain is featured by extracellular senile amyloid plaques, intraneuronal neurofibrillary tangles and extensive neuronal cell loss in specific regions of the brain associated with memory. The exact mechanism of neuronal cell dysfunction leading to the memory loss in AD is poorly understood. A number of studies have indicated that yeast is a suitable model system to decipher the molecular mechanisms involved in a variety of neurodegenerative disorders caused by pathological protein misfolding and deposition. Here, the knowledge from various studies that have utilized a yeast model to study the mechanism of pathways involved in AD pathogenesis is summarized. © 2010 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd. All rights reserved.